2021
DOI: 10.3389/fonc.2021.631991
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Stiffness: New Areas Affecting Cell Metabolism

Abstract: In recent years, in-depth studies have shown that extracellular matrix stiffness plays an important role in cell growth, proliferation, migration, immunity, malignant transformation, and apoptosis. Most of these processes entail metabolic reprogramming of cells. However, the exact mechanism through which extracellular matrix stiffness leads to metabolic reprogramming remains unclear. Insights regarding the relationship between extracellular matrix stiffness and metabolism could help unravel novel therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 127 publications
(165 reference statements)
2
70
0
Order By: Relevance
“…ECM is involved in cellular metabolism via regulating glucose, lipid, and amino acid metabolism [ 56 ]. Recent in-depth studies have shown that extracellular matrix stiffness has been implicated in BMSC differentiation via regulating energy metabolism [ 57 , 58 ].…”
Section: Environmental Stress Hormone Drugs and Biological/pathologic...mentioning
confidence: 99%
“…ECM is involved in cellular metabolism via regulating glucose, lipid, and amino acid metabolism [ 56 ]. Recent in-depth studies have shown that extracellular matrix stiffness has been implicated in BMSC differentiation via regulating energy metabolism [ 57 , 58 ].…”
Section: Environmental Stress Hormone Drugs and Biological/pathologic...mentioning
confidence: 99%
“… Amino acid, glucose, and lipid metabolism The effects of ECM stiffness on glucose metabolism are mediated by several pathways, of which the YAP/TAZ and FAs are predominant (see Figure 7). As reported by Ge et al, there are several other coupling pathways inducing modifications of nutrient metabolism, which will not be described in the following (for review, see [170]). Main glucose metabolism changes induced by extracellular stiffness are represented by changes in glucose uptake by GLUT transporters, regulation of glycolysis, regulation of the pentose phosphate pathway through the PI3K-AKT pathway, and glycogen metabolism through AMPK [174][175][176][177][178].…”
Section: The Link Between Extracellular Stiffness and Cell Metabolismmentioning
confidence: 99%
“…Among them, hyaluronan acid and collagens are the main determinants of ECM stiffness. Information derived from ECM stiffness can then be converted by the cells and influence their fate, particularly through changes in their metabolism [170]. One remarkable feature of cancer cells is the capacity to change their metabolism to adapt to the harsh conditions of their specific tumor environment and adapt to the aberrant signaling induced by oncogenes or tumor suppressors [171].…”
Section: Enrichment In Cancer Stem Cellsmentioning
confidence: 99%
“…CAFs exhibit diverse functions to sustain tumor growth including providing metabolic support to enable neoplastic proliferation. Recently, a connection between tissue mechanics and cell metabolism has been identified [ 91 , 116 ]. The mechanics and alterations in tumor stiffness were shown to influence the creatine-phosphagen ATP-recycling system, affecting ATP/ADP and ATP/AMP levels, and this was shown to play a role in tumor invasion, migration and metastasis of cancer cells [ 117 ].…”
Section: Emerging Role Of Biomechanics Influencing Pdac Metabolismmentioning
confidence: 99%